Konflik Dalam Perspektif Pendidikan Multikultural - Hermana Somantrie (Jurnal Pendidikan dan Kebudayaan, 2011)
Conflict is a potential of individual or group tension in multicultural societies because of their different perspectives and objectives between them. Conflict can be resulted from a simple problem to a complex problem. Conflict in some areas of Indonesia has become a chaotic condition. In one hand, most people use conflict as a mode to demonstrate frustrations and angers they feel; and in other and, those who use conflict as a gun for resolving problems they have. The implementation of multicultural education is an effort for conflict resolution, because conflict is no longer a phenomenon, but it has been a reality in a daily society’s life. Therefore, national education authority of Indonesia should propose the educational policy to prioritize the implementation of multicultural education, as an instrument to resolve some conflicts happening in society, nation, and state level.